Improving Linkages Through a Service-oriented Local Farmers–Hotel Supply Chain—An Explanatory Case in Grenada. Issue 4 (4th July 2018) - Thomas-Francois, Kimberly; Joppe, Marion; von Massow, Michael
ABSTRACT: Ensuring strong sectorial linkages exist with tourism and other sectors in the economy to retain and distribute tourism benefits to communities is often the goal of destination planners. While agriculture and tourism food linkage is considered, the literature suggests that farmer–hotel supply chain relationships are often weak, resulting in economic leakages due to high food importation to support the tourism sector, particularly in developing tourism destinations. The traditional transactional management of hotel supply chains fails to facilitate consistent and strong trade between the two sectors. Therefore, a service-oriented farmers–hotel supply chain is proposed, which places greater value on local food by making the local food part of the service experience. Research findings indicated that service-oriented approach through value co-creation, valued relationships and leveraging intangible resources embedded in local food although not fully exploited in this case study presents opportunities to improve and strengthen of local food supply chains.